Efficacy of whip roller setting on physical attributes of denim fabric - Farial Islam Farha; Fahmida Siddiqa; Md. Rashedul Islam (Fashion and Textiles, 2017)
Abstract Whip roller settings in a weaving machine is one of the vital factor to adjust warp yarn tension properly as well as delivering fault free fabric. The present study was undertaken with an aim to explore the influence of whip roller settings on various physical and mechanical properties of both grey and finished 100% cotton denim fabric in order to select suitable position of whip roller for producing particular (3/1 twill) denim fabric. For this purpose total eight positions of whip roller were selected keeping constant depth with variable height in five cases and constant height with variable depth in three cases. The samples were produced in an air jet loom and some prominence like EPcm, PPcm, areal density, tensile strength, dimensional stability, air permeability, crimp% and skewness were checked. Data analysis of all the results showed that with the ascendance of whip roller, crimp% of warp yarn was decreased whereas crimp% of weft yarn was increased both in grey and finished state. Decreasing the depth of whip roller caused increment of both warp and weft crimp% in both state. Tensile strength in warp way direction was found to increase gradually up to a certain roller height and then decreased whereas air permeability showed reverse trend in both state. Warp density, Weft density as well as areal density was also affected by the alteration in settings of whip roller. Due to reduction of roller depth, warp way tensile strength and lengthwise shrinkage were reduced but air permeability had improved.